Prevalence of Methicillin Resistant Staphylococcus Aureus Among Food Handlers in Duhok City - Abdulrahman, Masood A.; Taher, Arazoo I. (Science Journal of University of Zakho, 2018)
Food handlers harbouring S. aureus on their noses or in hands are considered as the main source of food contamination. Antibiotic resistance in S. aureus is a serious issue. The study aimed to find out the prevalence of methicillin-resistant S. aureus among food handlers in restaurants of Duhok city. Nasal and hand swabs were taken from 200 food handlers. The collected swabs inoculated on mannitol salt agar and incubated at 37oC for 24-48h. Isolates identified as S. aureus underwent antimicrobial sensitivity testing to methicillin and vancomycin on Mueller Hinton agar. A total of 74 (37%) out of 200 cultures of food handlers were found to be colonized with S. aureus.53 (26.5%) isolated from the nose, compared with 8 (4.0%) from hands and 13 (6.5%) from both. 27% of the food handlers were found to be MRSA carrier, and none of the isolates were resistant to Vancomycin. The study revealed a high prevalence of MRSA among food handlers in Duhok city. Food handlers in public places are required to go through regular screening for both nasal and skin carriage of S. aureusfor the early detection and treatment of carriers. So as to protect the community from staphylococcal food poisoning and the spread of resistant S. aureus strains among the population.
Keywords: MRSA; Food handlers; Prevalence; Duhok